Current Progress of RNA Aptamer-Based Therapeutics - Zhou, Jiehua (Frontiers Media S.A., 2012)
Aptamers are single-stranded nucleic acids that specifically recognize and bind tightly to their cognate targets due to their stable three-dimensional structure. Nucleic acid aptamers have been developed for various applications, including diagnostics, molecular imaging, biomarker discovery, target validation, therapeutics, and drug delivery. Due to their high specificity and binding affinity, aptamers directly block or interrupt the functions of target proteins making them promising therapeutic agents for the treatment of human maladies. Additionally, aptamers that bind to cell surface proteins are well suited for the targeted delivery of other therapeutics, such as conjugated small interfering RNAs (siRNA) that induce RNA interference (RNAi). Thus, aptamer-siRNA chimeras may offer dual-functions, in which the aptamer inhibits a receptor function, while the siRNA internalizes into the cell to target a specific mRNA. This review focuses on the current progress and therapeutic potential of RNA aptamers, including the use of cell-internalizing aptamers as cell-type specific delivery vehicles for targeted RNAi. In particular, we discuss emerging aptamer-based therapeutics that provide unique clinical opportunities for the treatment various cancers and neurological diseases.